Local scour around a cylinder due to waves and currents - Win, Aung; Shibayama, Tomoya; Suphat Vongvisessomjai; Tawatchai Tingsanchali; Government of Denmark (Bangkok : Asian Institute of Technology, 1991)
A new model is proposed for three-dimensional local scour on the basis of wave and current calculation around cylinder. The model consists of three submodels for calculating 1) wave field, 2) wave induced currents, and 3) sand transport and local topography change. Vortex formation and its effect to local scour is also included in the model. The initial bottom topography, geometry of the structure and incident wave condition are given as initial condition. Then the wave field around the structure is computed by using the linear diffraction theory. Computation of the wave induced currents follows that of the wave field. The mass transport velocity is calculated analytically by use of computed wave field. The steady current, induced by gradient of radiation stress, is determined through numerical calculation using depth integrated conservation equations of mass and momentum for the fluid motion. The wave and current fields thus computed are utilized in the submodel of sand transport and local topography change. The distribution of sand transport rates produce by wave and current are estimated and then the change of local bottom elevations are computed by solving the equation of sand mass conservation. The computed topography around the structure is compared with the measured topography of laboratory experiment, which was done by Saito et al. (1990). The comparison shows that some discrepancies exist especially in front of the structure and about at 130 degree from wave-current direction close to the cylinder. In order to improve model estimation, a vortex model is developed, since vortex formation is expected under the effect of steady flow induced by wave height distribution. After introducing the correction factor, the model gives a reasonable result. The result of the vortex model is superimposed with the main model. The superimposed result of the bottom topography is in good agreement with experimental results.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Waves -- Mathematical models; Scour (Hydraulic engineering)